EFEKTIFITAS PEMBERIAN TERAPI MUSIK INSTRUMENT TERHADAP KUALITAS TIDUR PASIEN GAGAL GINJAL KRONIK YANG MENJALANI HEMODIALISA - Eka Isranil Laily; Juanita, Juanita; Cholina Trisa Siregar (Fakultas Keperawatan-Universitas Syiah Kuala, 2015)
ABSTRAKPenyakit gagal ginjal kronik merupakan masalah kesehatan yang berkembang pesat. Pasien dengan hemodialisis memiliki masalah gangguan tidur yang berefek terhadap kualitas hidup pasien hemodialisis. Gangguan tidur memiliki dampak negatif pada respon imun dan dapat menyebabkan perkembangan kardiovaskuler yang merupakan penyebab kematian pada pasien gagal ginjal. Tujuan penelitian ini adalah untuk mengidentifikasi efektifitas pemberian terapi musik instrument terhadap kualitas tidur pasien gagal ginjal kronik yang menjalani hemodialisa. Penelitian ini menggunakan desain quasi-eksperimen dengan pre and post test with control dengan sampel 73 orang dengan menggunakan tabel power analysis 38 responden. Hasil penelitian menunjukkan adanya efek pemberian terapi musik instrument terhadap kualitas tidur pasien gagal ginjal kronik yang menjalani hemodialisa dengan hasil uji independent t test yaitu p=0,001 (p0,005). Perbandingan kualitas tidur sebelum dan sesudah pemberian terapi musik instrument menggunakan analisa data paired t-test dengan p=0,000. Kualitas tidur responden setelah dilakukan pemberian terapi musik instrument menunjukkan peningkatan.Kata Kunci: terapi musik, kualitas tidur, hemodialisaABSTRACTBreast cancer is the most common cancer suffered by women. Phenomenon in getting from patients treated with breast cancer who received chemotherapy in Haji Adam Malik Hospital, there is an increasing number of breast cancer throughout the year 2014 there were 9189 people. Patients with breast cancer is highest in North Sumatra Batak tribe women as much as 215 people (68.9%). The objective of this research was to explore the experience of Bataknese breast cancer patients who were under chemotherapy treatment. The research used phenomenology descriptive method. The data were gathered by conducting in-depth interviews. The sample were 15 Bataknese breast cancer patients who had fulfilled the criteria, taken by using purposive sampling technique. The Results of recorded interviews was analyzed by using content analysis. The result of the research showed that there were five themes which reflected the phenomena. They were experienced the emotional instability of breast cancer patients as a response to chemotherapy, adaptation to reduce the physical changes after chemotherapy, seeked the healing and recovery by breast cancer patients who were under chemotherapy treatment, reduced the emotional instability by breast cancer patienst who were under chemotherapy treatment, obstacles which is experienced by the breast cancer patients under chemotherapy treatment. It is recommended that health care provider, especially nurse, provide holistic service based on cultural for breast cancer patients who were treated with chemotherapy and give information to educational that the importance of cultural to give the nursing services.Keywords: Musical Therapy, Sleep Quality, Hemodialysis